2018
DOI: 10.1111/apa.14361
|View full text |Cite
|
Sign up to set email alerts
|

Early echocardiography does not predict subsequent treatment of symptomatic patent ductus arteriosus in extremely preterm infants

Abstract: Echocardiographic ductal parameters on day 1 or 3 did not identify infants who received PDA treatment. Gestation was the most powerful predictor for receiving medical or surgical treatment of PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our study reported a high spontaneous closure rate in infants born at 25 gestational weeks or later, consistent with recent reports [8,26]. Due to high treatment rates, we were not able to report the actual spontaneous rate in infants born before 25 gestational weeks in our cohort, but it has been reported to be relatively high in centers with a non-interventional PDA strategy [8,9,[26][27][28]. Furthermore, there was possible overtreatment as infants having three ibuprofen doses or less had a similar closure rate as infants who closed their duct spontaneously.…”
Section: Discussionsupporting
confidence: 89%
“…Our study reported a high spontaneous closure rate in infants born at 25 gestational weeks or later, consistent with recent reports [8,26]. Due to high treatment rates, we were not able to report the actual spontaneous rate in infants born before 25 gestational weeks in our cohort, but it has been reported to be relatively high in centers with a non-interventional PDA strategy [8,9,[26][27][28]. Furthermore, there was possible overtreatment as infants having three ibuprofen doses or less had a similar closure rate as infants who closed their duct spontaneously.…”
Section: Discussionsupporting
confidence: 89%
“…There are few studies on surgically treated PDA in infants born before 28 weeks gestational age, and results from studies of infants born at a higher gestational age might be difficult to apply in extremely pre-term infants. Also, many studies on surgically treated PDA were conducted during an era where surfactant therapy, antenatal steroids, non-invasive positive pressure ventilation, routine echocardiography, or pharmacological treatment of PDA were not fully established (14,15). The aim of this matched case control study of PDA was to investigate the differences in peri-and post-natal characteristics, pharmacological PDA treatment, and outcomes between surgically and non-surgically treated extremely preterm infants.…”
Section: Introductionmentioning
confidence: 99%